Dwelling Time and Its Impact on Logistics Costs and Competitiveness: Challenges and Policy Solutions in Indonesia - Anggraeni, Heni; Wardhana, Didin; Kushendar, Deden Hadi (Indonesian Journal of Social Science Research, 2025)
In the era of globalization and increasingly competitive trade, logistics efficiency plays a critical role in determining product pricing and strengthening national competitiveness. One of the major bottlenecks in Indonesia’s logistics chain is the prolonged dwelling time at ports — the duration between container unloading and its release from the terminal. This paper uses a descriptive qualitative approach to examine the economic and operational implications of dwelling time, drawing insights from both business practitioners and academic analyses. Findings reveal that extended dwelling time significantly increases logistics costs, disrupts production cycles, and weakens the market position of domestic products. Factors contributing to inefficiencies include bureaucratic complexity, physical inspection processes (behandle), limited port infrastructure, and inconsistent implementation of risk-based inspection systems. However, government initiatives such as the National Logistic Ecosystem (NLE) have demonstrated notable progress by reducing average national dwelling time to 2.6 days through digital integration and streamlined procedures. The study concludes that addressing dwelling time effectively requires a comprehensive strategy that involves infrastructure development, regulatory simplification, inter-agency collaboration, and enhanced use of digital platforms. These steps are essential to improve Indonesia’s trade efficiency and ensure a more competitive economic environment.